2004
DOI: 10.1108/01425450410511043
|View full text |Cite
|
Sign up to set email alerts
|

Work motivation and job satisfaction in the Nordic countries

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
78
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 24 publications
12
78
0
3
Order By: Relevance
“…They also describe the measures taken by the government to address the issue. Eskildsen, Kristensen and Westlund (2004) studied the differences in intrinsic work motivation and job satisfaction among employees with different characteristics working in Nordic countries. The authors found that job satisfaction and intrinsic work motivation have a nearly linear relationship with age and that the employees with higher education reported higher level of intrinsic work motivation.…”
Section: 4mentioning
confidence: 99%
“…They also describe the measures taken by the government to address the issue. Eskildsen, Kristensen and Westlund (2004) studied the differences in intrinsic work motivation and job satisfaction among employees with different characteristics working in Nordic countries. The authors found that job satisfaction and intrinsic work motivation have a nearly linear relationship with age and that the employees with higher education reported higher level of intrinsic work motivation.…”
Section: 4mentioning
confidence: 99%
“…Therefore, managers shouldn"t think that what will motivate them will also motivate the employees. Eskildsen et al (2003) studied the differences in intrinsic work motivation and job satisfaction among employees with different characteristics working in Nordic countries. The authors found that job satisfaction and intrinsic work 1884 motivation have a nearly linear relationship with age and that the employees with higher education reported higher level of intrinsic work motivation.…”
Section: Gender and E-leadership:-mentioning
confidence: 99%
“…Motivation can be effected by factors like job satisfaction, which has been found to have correlations with age [36].…”
Section: Project Relocationmentioning
confidence: 99%